A Single‐Year Cosmic Ray Event at 5410 BCE Registered in 14C of Tree Rings. Issue 11 (9th June 2021) - Miyake, F.; Panyushkina, I. P.; Jull, A. J. T.; Adolphi, F.; Brehm, N.; Helama, S.; Kanzawa, K.; Moriya, T.; Muscheler, R.; Nicolussi, K.; Oinonen, M.; Salzer, M.; et al.
Abstract: The annual 14 C data in tree rings is an outstanding proxy for uncovering extreme solar energetic particle (SEP) events in the past. Signatures of extreme SEP events have been reported in 774/775 CE, 992/993 CE, and ∼660 BCE. Here, we report another rapid increase of 14 C concentration in tree rings from California, Switzerland, and Finland around 5410 BCE. These 14 C data series show a significant increase of ∼6‰ in 5411–5410 BCE. The signature of 14 C variation is very similar to the confirmed three SEP events and points to an extreme short‐term flux of cosmic ray radiation into the atmosphere. The rapid 14 C increase in 5411/5410 BCE rings occurred during a period of high solar activity and 60 years after a grand 14 C excursion during 5481–5471 BCE. The similarity of our 14 C data to previous events suggests that the origin of the 5410 BCE event is an extreme SEP event. Plain Language Summary: The 14 C data of tree rings register extreme storms of solar energetic particles (SEPs), far larger than the largest SEP event ever observed in the Space Era. So far, three extreme SEP events have been reported as a rapid 14 C increase in tree rings and 10 Be and 36 Cl increases in ice cores. In this study, we found a new rapid 14 C increase in 5410 BCE using annual 14 C content in ring samples from California, Switzerland, and Finland. The 14 C signature of 5410 BCE event ties the origin of this 14 C excursion to an extreme SEP event similar to three other extreme SEP events (774/775 CE, 992/993 CE, and ∼660 BCE) confirmed with radionuclides of ice cores. Key Points: Rapid 14 C increase of ∼6‰ with significant level was found in tree rings from California, Switzerland, and Finland around 5410 BCE Five thousand, four hundred ten BCE event occurred during a period of high solar activity and 60 years after a grand 14 C excursion of ∼20‰ from 5481 to 5471 BCE The similarity of this 14 C signature to already known solar events suggests that the origin of this new 5410 BCE event is an extreme SEP